Relaxing at work: does virtual reality work? An exploratory study among employees in their workplace - Michinov, Estelle; Dodeler, Virginie; Adam, Hugo; Michinov, Nicolas (Frontiers in Organizational Psychology, 2024)
Introduction The development of virtual reality provides new opportunities for conducting relaxing activities in a simulated environment. Although studies on the effects of VR-based relaxation are developing, they have mostly been performed with students, and more rarely with employees. Methods This study aimed to examine the effects of VR relaxation exercises with employees. Forty-seven employees were divided into two conditions: Virtual Reality (n = 25) and 2D video (n = 22). Results The results indicate that relaxing activities reduced stress and negative emotions, while increasing perceived restoration using VR and 2D video. The acceptability and user experience were higher only in the VR condition. VR relaxation provides a sense of disconnection from the workplace that allows employees to increase the pleasant experience. Discussion The 2D solution, while less immersive, can be an alternative for employees for whom VR is not recommended. The question of inclusive digital tools is a key issue in the quality of working life programs.